2005
DOI: 10.1080/02699050500150104
|View full text |Cite
|
Sign up to set email alerts
|

The symptom checklist-90-revised and mild traumatic brain injury

Abstract: The results of this study suggest that the SCL-90-R has considerable utility as a general measure of psychological and symptomatic distress following MTBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Our current affective findings are also similar to a past report that showed increased self-reported anxiety levels in mild TBI participants compared with controls, only in a group of mild TBI participants who were unaware of their group membership, but not those made aware of their mild TBI status (Ozen & Fernandes, 2011). Prior studies have found increased levels of selfreported anxiety (Dischinger et al, 2009;Westcott & Alfano, 2005) and increased prevalence of anxiety-related disorders (Mooney & Speed, 2001) long after mild TBI. Our findings confirm that self-reported anxiety levels are heightened in individuals long after a mild TBI, even when "diagnosis threat" is an unlikely confound.…”
Section: The Importance Of Reducing the Influence Of Diagnosis Threatsupporting
confidence: 89%
See 1 more Smart Citation
“…Our current affective findings are also similar to a past report that showed increased self-reported anxiety levels in mild TBI participants compared with controls, only in a group of mild TBI participants who were unaware of their group membership, but not those made aware of their mild TBI status (Ozen & Fernandes, 2011). Prior studies have found increased levels of selfreported anxiety (Dischinger et al, 2009;Westcott & Alfano, 2005) and increased prevalence of anxiety-related disorders (Mooney & Speed, 2001) long after mild TBI. Our findings confirm that self-reported anxiety levels are heightened in individuals long after a mild TBI, even when "diagnosis threat" is an unlikely confound.…”
Section: The Importance Of Reducing the Influence Of Diagnosis Threatsupporting
confidence: 89%
“…Similar to the majority of previous reports, we did not expect any group differences to emerge on the neuropsychological tasks, nor on our cognitive self-report measures. We did anticipate, however, that mild TBI participants would report higher levels of anxiety compared with controls, a result previously reported in the mild TBI literature (Dischinger, Ryb, Kufera, & Auman, 2009;Westcott & Alfano, 2005) and in participants who were not exposed to "diagnosis threat" (Ozen & Fernandes, 2011).…”
Section: Introductionmentioning
confidence: 60%
“…As well, “neutral” MHI participants reported higher levels of state anxiety compared to “diagnosis threat” MHI participants. Prior studies have also found increased levels of self-reported anxiety (Dischinger et al, 2009; Westcott & Alfano, 2005) and increased prevalence of anxiety-related disorders (Mooney & Speed, 2001) long after MHI. This study adds to that literature in that higher anxiety levels were reported by high-functioning undergraduate students with a MHI following the completion of a neuropsychological test battery, but only when they were unaware the effects of their head injury were being investigated.…”
Section: Discussionmentioning
confidence: 93%
“…12 The SCL-90 is regularly used in TBI research 22,23 and has been found to be an effective measure of general distress. 24 It contains a 20-item depression subscale in which respondents report distress severity for each of 20 symptoms over the past week; response options are "not at all," "a little bit," "moderately," "quite a bit," or "extremely." The SCL-20 has excellent psychometric properties and is sensitive to change, particularly within medical samples.…”
Section: Symptom Checklist-20mentioning
confidence: 99%